Direct C–H amination reactions of arenes with N-hydroxyphthalimides catalyzed by cuprous bromide - Zhang, Dongming; Lv, Bin; Gao, Pan; Jia, Xiaodong; Yuan, Yu (Beilstein Journal of Organic Chemistry, 2022)
An efficient Cu-catalyzed strategy for the direct C–H amination of arenes in high yields using N-hydroxyphthalimide as the amidyl radical precursor under air is reported. A possible mechanism is proposed that proceeds via a radical reaction in the presence of CuBr and triethyl phosphite.
Keywords: amination; copper; N-hydroxyphthalimides; radical reactions; triethyl phosphite